Immigrant Evangelicalism in the COVID-19 Crisis: Reactions and Responses from Brazilian Evangelical Churches in Florida - Serrão, Rodrigo (International journal of Latin American religions, 2020)
This article seeks to analyze the reactions and responses of three churches of the Brazilian diaspora in Florida, United States, to the COVID-19 pandemic. Drawing on sermons posted on YouTube and Facebook in March, April, and May, we argue that Brazilian immigrant churches in Florida reacted to the pandemic in civil, theological, practical ways. We begin by providing a general introduction to evangelicalism in the United States and its influence in Brazilian evangelical life to give a historically sound background to the study. We also present the story of Brazilian migration to the United States. Then, we analyze the content posted in social media by pastors and churches of the Brazilian diaspora in the United States and other church leaders to ascertain their position regarding the responses to the COVID-19 crisis. Results show the churches responded to the pandemic in three primary ways: they adhered to authorities’ guidelines, provided sermons with apocalyptic undertones, and organized food pantries and donations for members in need.